Unpacking the Complexity of Gender Integration in the U.S. Military Using Discourse Analysis: The Case of Servicewomen’s Talk Around Having to Prove Themselves - Pawelczyk, Joanna (Studia Anglica Posnaniensia, 2021)
The findings of the micro-level analysis – interpreted through the lenses of tokenism and the category of the ‘honorary man’ – reveal women’s complex and nuanced struggle to fit and find acceptance in the military culture of hypermasculinity. They also re-engage with the ideas of tokenism by demonstrating that various acts of proving, reflecting women’s token status, may concurrently and paradoxically be a means to earn honorary man status.